KELAYAKAN USAHA INDUSTRI KEMPLANG ANEKA RASA SKALA KECIL DI KELURAHAN 5 ULU PALEMBANG - Maryani, Sri (Publikasi Penelitian Terapan dan Kebijakan, 2013)
As an icon of Palembang city, multi flavor kemplang has a great opportunity to be developed, both for promoting the local economy and increasing regional revenue in the tourism sector. The purpose of this study is to determine the feasibility of multiflavor kemplang industry in kelurahan 5 Ulu Palembang by using the conventional financial criteria include NPV, Net B / C and Pay Back Period, as well as non-financial methods that include technical feasibility, political feasibility, social feasibility,and feasibility for household main sourceof income. The study indicates that multiflavor home industry with minimum scale of 5 kg per day would be able to support the minimum cost of living, and to finance the education of 2 children up to the college level. Result shows that NPV is Rp.255.974.400,-. Net B/C is 2,31, and PBP is 0,79 which as a whole indicate that multiflavor kemplang home industry is feasible to be developed in kelurahan 5 Ulu Palembang